2009
DOI: 10.1007/s11661-009-9826-0
|View full text |Cite
|
Sign up to set email alerts
|

Paraequilibrium Carburization of Duplex and Ferritic Stainless Steels

Abstract: AISI 301 and E-BRITE stainless steels were subjected to low-temperature (743 K) carburization experiments using a commercial technology developed for carburization of 316 austenitic stainless steels. The AISI 301 steel contained~40 vol pct ferrite before carburization but had a fully austenitic hardened case,~20-lm thick, and a surface carbon concentration of~8 at. pct after treatment; this ''colossal'' paraequilibrium carbon supersaturation caused an increase in lattice parameter of~3 pct. The E-BRITE also de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 13 publications
2
18
0
Order By: Relevance
“…structure of metal atoms, while the maximum C content is ~19 at.% [59]. In expanded ferrite, obtained in ferritic stainless steels, a maximum N content of ~24 at.% was observed [60], and the reported maximum C content was ~10 at.% [61]. Similar values were detected in expanded martensite, with a maximum N content of ~22 at.% [62] and a maximum C content of ~10 at.% [63].…”
Section: N and C Solid Solutions In Fe Phases And Formation Of "Expan...supporting
confidence: 61%
“…structure of metal atoms, while the maximum C content is ~19 at.% [59]. In expanded ferrite, obtained in ferritic stainless steels, a maximum N content of ~24 at.% was observed [60], and the reported maximum C content was ~10 at.% [61]. Similar values were detected in expanded martensite, with a maximum N content of ~22 at.% [62] and a maximum C content of ~10 at.% [63].…”
Section: N and C Solid Solutions In Fe Phases And Formation Of "Expan...supporting
confidence: 61%
“…On the other hand, case hardening of austenitic stainless steels (ASS) by nitriding can be achieved by intensive precipitation of chromium nitrides (CrN, Cr 2 N) in the diffusion zone during nitriding at temperatures around 500 o C, increasing hardness up to 1400 HV, but decreasing the corrosion resistance [Larisch, 1999], Czerwiec, 2000], [Liang, 2000]. However, when low temperature nitriding is used, close to 400 o C, the hardening mechanism changes from nitride precipitation to lattice distortion of the FCC austenitic phase, leading to formation of expanded austenite, with hardness close to 1400 HV and no loss of corrosion resistance [Fewell, 2000], Borgioli, 2005], [Mingolo, 2006]. The hardening mechanism is related to high compressive residual stresses arisen from lattice distortion.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior was attributed to the higher content of chromium in the ferritic phase [Christiansen, 2005]. [Michal, 2009], on the other hand, found that after low temperature plasma carburizing an AISI 301 stainless steel, containing approximately 40% of ferrite, the ferrite peaks disappeared and the austenite peaks have shifted to smaller 2q angles, indicating an expansion of ~3 % on the lattice parameter of austenite.…”
Section: Introductionmentioning
confidence: 99%
“…"Low," in this context, means low enough to suppress carbide precipitation by immobilizing Cr, but still high enough to enable carbon diffusion into technically useful depths within industrially feasible processing times. Idealizing these nonequilibrium conditions as a state with no metal atom mobility at all, the system is then confined to a trajectory leading to a "carbon paraequilibrium", rather than conventional thermodynamic (or "ortho") equilibrium [3]. With this approach, treatment times of order 0.1 Ms (1 day) can infuse carbon to an average depth z ≈ 10 µm.…”
Section: Introductionmentioning
confidence: 99%